PERNIKAHAN PENDERITA HIV AIDS DALAM TINJAUAN MAQASHID SYARIAH - Inas Afanin; Muhsan Syarafuddin (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2023)
Marriage with HIV AIDS causes danger because the disease can transmit to their partners and offspring. On the other, PLWHA still has biological needs that need to fulfilled. The life of PLWHA to fight disease creates new problems in their future married life. Therefore, it needs to research the complications in PLWHA marriages and analyze PLWHA marriages in a review of maqashid sharia to find out how goodness be realized. This research uses the library method by reading and collecting data related to research objects from print and online media. The collected data were analyzed using qualitative methods and presented in deductive paragraphs. The result is complications of PLWHA marriage are economic problems, physical and psychological health, social, and complicated sexual and hereditary problems. The law of PLWHA marriage prohibited because they included ad-darar al-'am or general dangers that could harm other people. That is in line with maqashid sharia sad az-zariah or preventing damage. However, when someone accepts PLWHA and the impact on his marriage to PLWHA, marriage is allowed on condition that he can maintain maqashid sharia, there are protecting religion, soul, offspring, mind, and property. Meanwhile, marriage between PLWHA and PLWHA are more recommended because the harmless and they do not tyrannize other people.